Impact of process parameters on the mechanical and surface properties of AA6082 - Bilgehan Tunca; Bahadır Karaca (Acta Polytechnica)
This study investigates the effects of chemical composition, heat treatment, and processing parameters on the mechanical properties, microstructure, and surface quality of AA6082 aluminium alloy. Three castings with varying Mg and Si content were subjected to homogenisation at 580 °C for 8 and 10 hours, followed by extrusion and artificial ageing at 180 °C for 6, 8, and 10 hours, yielding 18 samples. Tensile testing, microstructural analysis, SEM examination, and anodic oxidation (18 V, 26–32 minutes) were conducted to assess performance. Results revealed that the highest tensile strength (361MPa) and yield strength (332 MPa) were achieved with 8-hour homogenisation and ageing (B2 sample), attributed to optimal β′′ precipitate formation, finer grain sizes, and a favourable composition (Mg: 0.92 %, Si: 1.09 %). The surface quality and hardness were enhanced by water shock and nitrogen gas cooling during extrusion, while the 10-hour homogenisation reduced porosity but increased the risk of overageing. SEM analysis confirmed ductile fracture in high-strength samples, and anodising produced thicker (11.7 μm), glossier coatings with longer processing times. These findings highlight the critical interplay of heat treatment duration, cooling strategies, and surface finishing in optimising AA6082 for industrial applications, with implications for process design and alloy development.